Early Use of the NMDA Receptor Antagonist Ketamine in Refractory and Superrefractory Status Epilepticus - F. A. Zeiler (Critical Care Research and Practice)
Refractory status epilepticus (RSE) and superrefractory status epilepticus (SRSE) pose a difficult clinical challenge. Multiple cerebral receptor and transporter changes occur with prolonged status epilepticus leading to pharmacoresistance patterns unfavorable for conventional antiepileptics. In particular, n-methyl-d-aspartate (NMDA) receptor upregulation leads to glutamate mediated excitotoxicity. Targeting these NMDA receptors may provide a novel approach to otherwise refractory seizures. Ketamine has been utilized in RSE. Recent systematic review indicates 56.5% and 63.5% cessation in seizures in adults and pediatrics, respectively. No complications were described. We should consider earlier implementation of ketamine or other NMDA receptor antagonists, for RSE. Prospective study of early implementation of ketamine should shed light on the role of such medications in RSE.